Acute neurological consequences of novel psychoactive substance use: a retrospective review in a large UK hospital. Issue 3 (2021) - Tanti, Matthew; Cosgrove, Jeremy; Kelleher, Charles; Jones, Rebekah; Maguire, Melissa
No abstract available